Psychometric properties of the coping with pre-exam anxiety and uncertainty scale in chilean university students - Guerra Díaz, Felipe (2021)
The present instrumental study aimed to describe the psychometric properties of the Coping with Pre-Exam Anxiety and Uncertainty Scale (COPEAU-A) in Chilean university students. 230 first-year students from a university in the north of Chile participated, where 67,4% were women and 32.6% men, with an average age of 18,9 years. By confirmatory factor analysis, using a robust weighted least squares method (WLSMV), five models were compared, finding the best fit indicators in the composite of four oblique factors with 20 ítems (X2=228,795, gl=164, p<,01; X2/gl=1,395; TLI=,929; CFI=,939; RMSEA=,042). The reliability of the four factors was adequate, showing McDonald's Omega coefficients between ω=,716 and ω=,873. In turn, the results showed the factorial invariance of the instrument according to sex. It is concluded that the psychometric properties of COPEAU-A would support its use to evaluate coping strategies in the face of anxiety and pre-exam uncertainty in Chilean university students who are beginning their academic careers.